2020
DOI: 10.1111/jfbc.13198
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐atopic dermatitis effects of hydrolyzed celery extract in mice

Abstract: This study investigated the ameliorative effects of acid hydrolyzed celery extract (HCE) and celery extract (CE) in an atopic dermatitis (AD) mice model. The results of the study showed that HCE, more than CE improved AD‐like skin lesions caused by fluoro‐2,4‐dinitrobenzene and house dust mite antigen administration. Further analysis also showed the dominance of HCE than CE in preventing mast cell infiltration in the dermis; inhibiting the IL‐31 expression in mice skin and reducing the immunoglobulin‐E, IL‐4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
9
0
2
Order By: Relevance
“…Although the exact mechanisms are not clear, it is possible that the apigenin-induced FLG upregulation could result from its antioxidant properties [ 206 ]. A more recent study in a mice model of AD revealed that both apigenin and other biologically active compounds present in celery, apigetrin and luteolin have ameliorative effects on AD signs and symptoms [ 207 ]. Additionally, apigenin has been suggested to be a promising agent for itch-reducing therapy, through its modulation of the IL-31 cytokine [ 208 ].…”
Section: Acquired Flg Deficiency–regulation Of Flg Expressionmentioning
confidence: 99%
“…Although the exact mechanisms are not clear, it is possible that the apigenin-induced FLG upregulation could result from its antioxidant properties [ 206 ]. A more recent study in a mice model of AD revealed that both apigenin and other biologically active compounds present in celery, apigetrin and luteolin have ameliorative effects on AD signs and symptoms [ 207 ]. Additionally, apigenin has been suggested to be a promising agent for itch-reducing therapy, through its modulation of the IL-31 cytokine [ 208 ].…”
Section: Acquired Flg Deficiency–regulation Of Flg Expressionmentioning
confidence: 99%
“…A previous study reported that CA‐treated wheat germ extract enhanced the anti‐inflammatory activity of wheat germ (Jeong et al., 2017). Hydrochloric acid‐hydrolyzed celery extract was shown to have improved anti‐inflammatory activities and ameliorated atopic dermatitis‐like symptoms in primary splenocytes and mice (Che et al., 2020; Shin et al., 2019). Several enzymes have been employed for the extraction of targeted bioactive flavonoids from plants including citrus peels, grapes, and apples (Gómez‐García et al., 2012; Li et al., 2006; Zheng et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The key flavonoid in celery has been identified as apigenin, which is present in aglycone and glycoside forms such as apiin (apigenin-7-apioglucoside) and apigetrin (apigenin-7-glucoside). Compared to its glycosides, apigenin has been reported to have more potent bioactivity in the form of stronger anti-inflammatory [2] and antioxidant [3] properties. Apigenin has also independently garnered interest due to its wide range of pharmacological benefits including anti-carcinogenic and anti-toxicant effects [4].…”
Section: Introductionmentioning
confidence: 99%